JOVAN CVIJIć AND THE FOUNDING OF KARST GEOMORPHOLOGY - Ford D. (My University, 2007)
Jovan Cvijić was born in western Serbia and studied widely in the Dinaric Kras. His publication of Das Karstphänomen (1893) established that rock dissolution was the key process and that it created most types of dolines, “the diagnostic karst landforms”. The Dinaric Kras thus became the type area for dissolutional landforms and aquifers; Germanicised as “karst”, the regional name is now applied to modern and paleo-dissolutional phenomena worldwide. Cvijić related the complex behaviour of karstic aquifers to development of solutional conduit networks and linked it to a cycle of landform evolution. He is recognized as “the father of karst geomorphology”.
Keywords: MESSINIAN; ADRIATIC COAST; KARST LANDSCAPE; CONDUIT NETWORK; KARST ROCK; Cenozoic::Neogene::Miocene::Messinian; Кайнозой::Неоген::Миоцен::Мессинский